Investigation of Food that Boost Immunity and Fight Infections in Humans Body in Akwa Ibom State (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The study investigated “food that boost immunity and fight infections in human’s body”. In carrying out the research descriptive survey design was adopted for the study. The study was carried out in Akwa Ibom State. The targeted population for the study comprised all medical personnels and microbiologists in Akwa Ibom State. A stratified random sampling technique was used to select 30 medical personnel, 10 from each of the three senatorial districts in Akwa Ibom and 15 microbiologists, 5 from each senatorial districts in the State, which gave a total of 135 respondents used for the study. The instrument used for data collection was a structured questionnaire titled “Immunity and Food Wellness Questionnaire (IFWQ)”. Face and content validation of the instrument was carried out by an expert in test, measurement, and evaluation in order to ensure that the instrument has the accuracy, appropriateness, and completeness for the study under consideration. The reliability coefficient obtained was 0.88, which was high enough to justify the use of the instrument. The data generated for this study was subjected to appropriate statistical technique such percentage analysis to answer research questions. The findings of the research revealed that Water-Hydration and Immunity” is essentially and majorly consumed by the residents in Akwa Ibom State among other for substances and this help them in boosting immunity and fighting infections in their bodies. The findings similarly also revealed that residents in Akwa Ibom consume food that boost immunity and fight infections in their bodies at very high extent. Finally, Akwa Ibom State residents consume water more than any other type of food that to boost immunity and fight infections. Also the people consume food that boost immunity and fight infections in their bodies to very high extent. The study concluded that humans have the potential to reduce the burden of infectious diseases and promote health and well-being across populations. However, one of the recommendations was that researchers should advance their understanding of the complex relationship between food and immunity and to contributing to the development of evidence-based dietary interventions that enhance infection resistance and promote overall health and well-being.